Purification, and activity of Human rhinovirus 3C protease fused with N-terminal GST-tag and C-terminal His-tag (GST-HRV3C-His) expressed in Escherichia coli - Le , Duong Vuong; Le , Thi Tuong Vy; Phan , Thi Phuong Trang; Nguyen , Duc Hoang (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
The Human rhinovirus 3C protease (HRV3C) is one of the most effective enzymes for removing fusion tag in purification process. This protease is often produced as fusion form GST-HRV3C but there is no study about the fusion form: GST-HRV3C-His. In this study, researchers conducted the purification GST-HRV3C-His expressed in E. coli, checked the activity and investigated its application. GST-HRV3C-His could be purified using His-tag column with 86.6% purity and GST column with 96.87%. The specific activity of GST-HRV3C-His was demonstrated to be about 4500 U/mg and its application in the purification of another proteins carrying HRV3C-specific recognition sequence, LEVLFQ¯GP based on His-tag or GST-tag was also proved in this study.